2021
DOI: 10.3390/pathogens10070793
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Human Papillomavirus Lifecyle through Post-Translational Modifications of the Viral E2 Protein

Abstract: The human papillomavirus (HPV) is a DNA tumor virus that infects cutaneous and mucosal epithelia where high-risk (HR) HPV infections lead to cervical, oropharyngeal, and anogenital cancers. Worldwide, nearly 5% of all cancers are caused by HR HPV. The viral E2 protein is essential for episomal replication throughout the viral lifecycle. The E2 protein is regulated by phosphorylation, acetylation, sumoylation, and ubiquitination. In this mini-review, we summarize the recent advancements made to identify post tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Acetylation of Tat, a human immunodeficiency virus HIV-1 protein, the influenza A protein NP, and the pUL26 protein of the human cytomegalovirus affects virulence properties, production of viral proteins, and virus replication and assembly ( Kumar et al., 2020 ; Murray et al., 2019 ). Interestingly, it has been demonstrated that the E2 protein of papillomaviruses is acetylated by p300 ( Jose et al., 2021 ) and that methylated non-structural protein 1 (NS1) from H3N2-subtype influenza A binds to histone readers ( Marazzi et al., 2012 ; Qin et al., 2014 ; Zhang et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation of Tat, a human immunodeficiency virus HIV-1 protein, the influenza A protein NP, and the pUL26 protein of the human cytomegalovirus affects virulence properties, production of viral proteins, and virus replication and assembly ( Kumar et al., 2020 ; Murray et al., 2019 ). Interestingly, it has been demonstrated that the E2 protein of papillomaviruses is acetylated by p300 ( Jose et al., 2021 ) and that methylated non-structural protein 1 (NS1) from H3N2-subtype influenza A binds to histone readers ( Marazzi et al., 2012 ; Qin et al., 2014 ; Zhang et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of viral proteins can have a significant impact on infection by both RNA and DNA viruses, their replication and cytotoxicity in a host cell. In fact, phosphorylation may regulate interactions between viral proteins and the viral genome throughout the well-orchestrated viral life cycle, viral protein stability, as well as virus–host interactions [ 98 , 99 ]. This is true for the SARS-CoV-2 virus also, where many phosphorylation sites have already been predicted for several SARS-CoV-2 proteins, including ORF3 proteins [ 38 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…81 HPV-16 and -31 E2 also bound several FGFRs, suggesting that FGFRs are important in regulating tissue differentiation-dependent replication of Papillomaviruses. 82 Chronic hepatitis C is a predisposing condition for liver cancer caused by infection by HCV. Infection by HCV is favoured by FGF2.…”
Section: Oncogenic Virusesmentioning
confidence: 99%
“…For bovine Papillomavirus, viral protein E2, responsible for activation of replication and transcription, was shown to be regulated by FGFR‐mediated phosphorylation 81 . HPV‐16 and ‐31 E2 also bound several FGFRs, suggesting that FGFRs are important in regulating tissue differentiation‐dependent replication of Papillomaviruses 82 …”
Section: Viral Infection and Fgfsmentioning
confidence: 99%